2011
DOI: 10.1680/geot.8.p.087
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductivity and compressibility of mixtures of Nagoya clay with sand or bentonite

Abstract: In this study, a series of incremental loading oedometer tests and microscopic observations is carried out in order to investigate the influence of sand/bentonite fractions on hydraulic conductivity and compressibility. If sand particles do not form a skeletal structure, and each particle is independent in the clay matrix, an additive fraction of sand causes a decrease in the compressibility; however, it does not affect the hydraulic conductivity under the same consolidation pressure. The additive fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…This method to determine hydraulic conductivity is accepted extensively (Sivapullaiah et al, 2000;Chai et al, 2004;Horpibulsuk et al, 2007;Yong et al, 2009;Watabe et al, 2011;Fan et al, 2014b), and therefore it is used in this study for relative comparison of hydraulic conductivity of various zeolite-amended clayey soil/Ca-bentonite backfills.…”
Section: Methodsmentioning
confidence: 99%
“…This method to determine hydraulic conductivity is accepted extensively (Sivapullaiah et al, 2000;Chai et al, 2004;Horpibulsuk et al, 2007;Yong et al, 2009;Watabe et al, 2011;Fan et al, 2014b), and therefore it is used in this study for relative comparison of hydraulic conductivity of various zeolite-amended clayey soil/Ca-bentonite backfills.…”
Section: Methodsmentioning
confidence: 99%
“…This structural arrangement can resist the effective vertical compressive stress in a better way as compared to Fig. 3 Flexible wall permeameter and consolidometer for consolidation and hydraulic conductivity tests the condition of sand particles that exists in a clay matrix with a higher bentonite content [35].…”
Section: Compression Index (C C )mentioning
confidence: 99%
“…In this regard, different clay fractions were used to make several cylindrical samples and pre-loaded before conducting falling head permeability tests and compression tests to determine the relevant permeability and compressibility properties. These properties were then compared to previous data (Simpson and Evans 2016;Watabe et al 2011) as shown in Figure 8. The current test results agree well with previous data.…”
Section: Theoretical Model Validation By Physical Modellingmentioning
confidence: 99%